Electrical Impedance Monitoring of Photothermal Porated Mammalian Cells. (February 2014) - Yamane, Daisuke; Wu, Yi-Chien; Wu, Ting-Hsiang; Toshiyoshi, Hiroshi; Teitell, Michael A.; Chiou, Pei-Yu
To transfer large cargo into mammalian cells, we recently provided a new approach called a photothermal nanoblade. Micron-sized membrane pores generated by the nanoblade are surprisingly well repaired with little cell death, suggesting rapid membrane-resealing dynamics. Here, we report the resealing time of photothermal porated mammalian cell plasma membranes using an electrical impedance sensor. Cell membrane pores were generated by high-speed cavitation bubbles induced by laser pulsing of metallic microdisks on a pair of transparent indium tin oxide electrodes. Electrical responses from the sensor electrodes were obtained with a signal voltage of 500 mV and a frequency at 500 kHz. Real-time impedance measurements show that membrane resealing and impedance recovery take a surprisingly long 1 to 2 min after laser pulsing. A nonrecovering impedance shift is also detected for cells after high-energy laser pulsing. This impedance response is also confirmed by a separate experiment in which thin-film gold electrodes are used to trigger cavitation bubbles for opening transient membrane pores on cells cultured on electrodes. Overall, our study platform provides new insight for micron-sized membrane defect repair dynamics to maintain cell viability.